Porous carbon material, preparation method of porous carbon material, silicon-carbon composite negative electrode material and application of silicon-carbon composite negative electrode material
A method for preparing porous carbon materials with controlled pore size and oxygen content addresses the challenges of silicon deposition in lithium-ion batteries, enhancing the performance of silicon-carbon composite electrodes through uniform deposition and improved cycle stability.
Patent Information
- Application Number
- CN202310774283.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-27
AI Technical Summary
Existing carbon-based materials for lithium-ion battery negative electrodes face issues with silicon deposition leading to poor cycle performance, low initial coulombic efficiency, and limited reversible capacity due to non-uniform distribution and expansion of elemental silicon.
A method to prepare a porous carbon material by dispersing an organic precursor with an alkali source and cross-linking agent, followed by activation and carbonization, to achieve uniform silicon deposition and control pore size, oxygen content, and surface state, resulting in a silicon-carbon composite with improved coulombic efficiency and capacity.
The method enables high-capacity, stable silicon-carbon composite electrodes with enhanced first coulombic efficiency and cycle stability by ensuring uniform silicon deposition and minimizing silicon oxide formation.
Smart Images

Figure BDA0004309015640000071
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of lithium-ion batteries, and in particular to a porous carbon material and a preparation method thereof, a silicon-carbon composite negative electrode material and applications thereof. Background Art
[0002] Currently, the carbon-based materials that can be used for the deposition of elemental silicon in the negative electrode of lithium batteries mainly include carbon black, graphite and resin pyrolytic carbon.
[0003] For single-substance silicon deposited carbon black materials, the single-substance silicon deposited on its surface is mostly attached to the carbon-based surface in the form of nanoparticles. During the cycle, the single-substance silicon is easily separated from the carbon-based due to expansion and pulverization, resulting in poor cycle performance of lithium-ion batteries and low initial coulombic efficiency. The method of preparing lithium-ion negative electrodes by depositing single-substance silicon on graphite as a matrix has been developed for more than 20 years (Journal of Applied Physics 77, 2363 (1995)). The early method mainly forms discretely distributed deposited single-substance silicon particles on the surface of graphite particles. In recent years, by adding a certain amount of ethylene and other molecules to the silicon source gas (Nature Energy 6, 1164 (2021)), the deposition process is controlled to achieve the formation of a continuous deposition layer of single-substance silicon on the surface of graphite particles, which effectively improves its low initial coulombic efficiency and poor cycle performance. However, due to the configuration of graphite materials, it is difficult to deposit a large amount of silicon, so there is still a problem of low reversible capacity. Porous carbon materials have high capacity and specific surface area, so they are currently also used as silicon deposition matrix materials (202111277420.0, 202111277556.1). The deposition of elemental silicon on them is also mainly dispersed nucleation, and the distribution dispersion is relatively high. Therefore, although higher capacity and first efficiency can be achieved, they decay severely within the first twenty cycles, with only 42%-53% of the first reversible capacity.
[0004] Therefore, it is necessary to develop suitable carbon-based materials on which elemental silicon can be uniformly deposited in large quantities to synthesize silicon-carbon materials with high first coulombic efficiency, high capacity and good cycle stability. Summary of the invention
[0005] In order to solve the above technical problems, the present disclosure provides a porous carbon material and a preparation method thereof, a silicon-carbon composite negative electrode material and applications.
[0006] In a first aspect, the present disclosure provides a method for preparing a porous carbon material, the preparation method comprising the following steps:
[0007] (1) dispersing an organic precursor in a solvent, then mixing with an alkali source and a cross-linking agent, and drying to obtain a pretreated product;
[0008] (2) Activating and carbonizing the pretreated product to obtain the porous carbon material.
[0009] The preparation method provided by the present disclosure can regulate the specific surface area and pore size distribution of the porous carbon material, and can also regulate the oxygen content and state of the surface thereof, so that the porous carbon material finally obtained can uniformly deposit elemental silicon to form a large number of uniform deposition layers. Specifically:
[0010] In step (1) provided in the present disclosure, the (soluble) polymer dispersed in the solvent (preferably water) is more likely to be in uniform and sufficient contact with the base, additives and cross-linking agent, thereby ensuring that after mixing and drying, a carbonized precursor with a certain molecular structure and composition can be obtained, in which the alkali source and the cross-linking agent are uniformly distributed, and after carbonization treatment, it is easy to have a more porous structure (including open pores and closed pores).
[0011] The purpose of step (2) provided in the present disclosure is to perform additional pore creation, pore expansion, and opening of closed pores. Through step (2) provided in the present disclosure, the finally obtained carbon material can have a larger specific surface area.
[0012] As a preferred technical solution of the present disclosure, the step (1) also includes: after dispersing the organic precursor in the solvent, adding an additive, preferably the added mass of the additive is 1%-10% of the mass of the organic precursor, for example 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc., and preferably the solvent is water.
[0013] The additives provided by the present disclosure can change the composition characteristics of the inner and outer surfaces of the pores of the product carbon, and can make the finally obtained porous carbon material have a better affinity with elemental silicon, thereby ensuring that the elemental silicon can be evenly deposited on the surface of the porous carbon material in the future.
[0014] As a preferred technical solution of the present disclosure, the additive is selected from silicate compounds.
[0015] As a preferred technical solution of the present disclosure, the organic precursor is selected from soluble phenolic polymers.
[0016] As a preferred technical solution of the present disclosure, the alkali source is selected from any one of ammonia water, urea or sodium carbonate, or a combination of at least two of them.
[0017] As a preferred technical solution of the present disclosure, the cross-linking agent is selected from hexamethylenetetramine and / or bisphenol cross-linking agents.
[0018] As a preferred technical solution of the present disclosure, in step (1), the amount of the alkali source added is such that the pH value of the mixed solution after mixing is 7.5-9, for example, 7.6, 7.7, 7.8, 7.9, 8, 8.2, 8.5, 8.8, etc.
[0019] As a preferred technical solution of the present disclosure, the mass ratio of the organic precursor to the cross-linking agent is 1:0.1-1, for example, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, etc.
[0020] As a preferred technical solution of the present disclosure, the step (2) comprises:
[0021] The pretreated product is mixed with zinc chloride, activated at 300-450°C (e.g. 320°C, 350°C, 380°C, 400°C, 420°C, etc.) for 1-1.5h (e.g. 1.1h, 1.2h, 1.3h, 1.4h, etc.), programmed to rise to 1200-1400°C (e.g. 1250°C, 1300°C, 1350°C, etc.) for carbonization for 0.5-2h (e.g. 0.8h, 1h, 1.2h, 1.5h, 1.8h, etc.) to obtain the porous carbon material.
[0022] or:
[0023] The pretreated product is mixed with zinc chloride, carbonized at 1200-1400°C (e.g. 1250°C, 1300°C, 1350°C, etc.) for 0.5-2h (e.g. 0.8h, 1h, 1.2h, 1.5h, 1.8h, etc.), and then mixed with hydroxide, activated at 700-900°C (e.g. 750°C, 800°C, 850°C, etc.) for 0.5-2h (e.g. 0.8h, 1h, 1.2h, 1.5h, 1.8h, etc.) to obtain the porous carbon material.
[0024] or:
[0025] The pretreated product is mixed with zinc chloride, and activated for the first time at 300-450°C (e.g., 320°C, 350°C, 380°C, 400°C, 420°C, etc.) for 1-1.5h (e.g., 1.1h, 1.2h, 1.3h, 1.4h, etc.), and programmed to rise to 1200-1400°C (e.g., 1250°C, 1300°C, 1350°C, etc.) for carbonization for 0.5-2h (e.g., 0.8h, 1h, 1.2h, 1.5h, 1.8h, etc.), and then mixed with hydroxide, and activated for the second time at 700-900°C (e.g., 750°C, 800°C, 850°C, etc.) for 0.5-2h (e.g., 0.8h, 1h, 1.2h, 1.5h, 1.8h, etc.) to obtain the porous carbon material.
[0026] As a preferred technical solution of the present disclosure, in the step (2), the activation and carbonization are both carried out under an inert atmosphere, preferably nitrogen or argon.
[0027] In the present disclosure, activation can form pores in the carbon material, while the carbonization process can increase the carbon content of the carbon material. The two steps are coordinated, and zinc chloride, which can play a role in dehydration, cross-linking and regulating the distribution of micropores, and hydroxide, which can expand and form pores through etching, are used at the same time, so that the finally obtained porous carbon material can well meet the application requirements.
[0028] As a preferred technical solution of the present disclosure, the mass ratio of the pretreatment product to zinc chloride is 1:2-6, for example, 1:3, 1:4, 1:5, etc.
[0029] As a preferred technical solution of the present disclosure, the mass ratio of the pretreatment product to the hydroxide is 1:1-6, for example, 1:2, 1:3, 1:4, 1:5, etc.
[0030] As a preferred technical solution of the present disclosure, the hydroxide is selected from any one of potassium hydroxide, sodium hydroxide or lithium hydroxide, or a combination of at least two of them.
[0031] In the present disclosure, step (1) may be route p1 or route p2:
[0032] Route p1: The organic precursor is dispersed in water, and then the additive is added and mixed for 1-6 hours, and then the alkali source and the cross-linking agent are added and mixed thoroughly for 1-12 hours, washed, dried, and set aside.
[0033] Route p2: The organic precursor is dispersed in water, and then an alkali source and a cross-linking agent are added and mixed thoroughly for 1-12 hours, washed, dried, and set aside.
[0034] In step (1), it should be noted that, regardless of route p1 or route p2, after all materials are mixed, the pH value of the mixed system needs to be maintained between 7.5 and 9.
[0035] In the present disclosure, step (2) can be route c1, route c2 or route c3:
[0036] Route c1: The pretreatment product is mixed with zinc chloride in a mass ratio of 1:2-6, heated to 300-450°C and kept for 1-1.5 hours for activation, and then programmed to heat to 1200-1400°C and kept for 0.5-2 hours.
[0037] Route c2: The pretreated product is heated to 1200-1400° C. and kept warm for 0.5-2 h, then mixed with potassium hydroxide in a mass ratio of 1:1-6, heated to 700-900° C. and kept warm for 0.5-2 h to activate, thereby obtaining the porous carbon material.
[0038] Route c3: The pretreatment product is mixed with zinc chloride in a mass ratio of 1:2-6, heated to 300-450°C and kept warm for 1-1.5h for activation, then heated to 1200-1400°C and kept warm for 0.5-2h, and then mixed with potassium hydroxide in a mass ratio of 1:1-6, heated to 700-900°C and kept warm for 0.5-2h for activation to obtain the porous carbon material.
[0039] In step (1) and step (2), route p1 and route p2 can be used in combination with route c1, route c2 and route c3 to obtain the porous carbon material described in the present disclosure.
[0040] In a second aspect, the present disclosure provides a porous carbon material prepared by the preparation method described in the first aspect.
[0041] As a preferred technical solution of the present disclosure, the specific surface area of the porous carbon material is 50-2500m 2 / g, the pore size of the pores on the surface is 0.7-100nm, the total surface oxygen content is ≤15wt%, for example 8%, 10%, 12%, 14%, etc., and the double bond oxygen content does not exceed 60% of the total oxygen content, for example 58%, 55%, 50%, 45%, 40%, 35%, 30%, etc.
[0042] The specific surface area described in the present disclosure refers to the distribution of specific surface area, and the pore size refers to the pore size distribution.
[0043] In the preparation method provided by the present disclosure, through pretreatment and subsequent activation and carbonization, on the one hand, the oxygen content in the product can be regulated, and on the other hand, the state of oxygen in the surface functional groups of the product can be adjusted, so that a large amount of uniform deposition layer can be formed during the deposition of elemental silicon on the surface of the porous carbon material; and the generation of silicon oxide and silicon carbide can be effectively controlled, so that the first coulombic efficiency, capacity, and cycle performance stability of the formed silicon-carbon composite negative electrode material can be improved.
[0044] In a third aspect, the present disclosure provides a silicon-carbon composite negative electrode material, wherein components of the silicon-carbon composite negative electrode material include the porous carbon material described in the second aspect and elemental silicon deposited on the surface of the porous carbon material.
[0045] In a fourth aspect, the present disclosure provides a negative electrode sheet, characterized in that it comprises the porous carbon material described in the second aspect or the silicon-carbon composite negative electrode material described in the third aspect.
[0046] In a fifth aspect, the present disclosure provides an electrochemical device, characterized in that it comprises the porous carbon material described in the second aspect or the silicon-carbon composite negative electrode material described in the third aspect or the negative electrode sheet described in the fourth aspect.
[0047] In a sixth aspect, the present disclosure provides a vehicle, characterized in that it comprises the negative electrode sheet described in the fourth aspect or the electrochemical device described in the fifth aspect.
[0048] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:
[0049] (1) The preparation method provided by the present disclosure is simple and easy to implement, and the method provided by the present disclosure can regulate the pore size distribution of the porous carbon material, and can also regulate the oxygen content and the state of oxygen in the porous carbon material, so that the porous carbon material finally obtained has a better application effect;
[0050] (2) The porous carbon material provided by the present invention can form a large amount of uniform deposition layer when elemental silicon is deposited on its surface. At the same time, the porous carbon material provided by the present invention can effectively control the production of silicon oxide and silicon oxide, thereby making the finally formed silicon-carbon composite negative electrode material have excellent first coulombic efficiency and capacity, and high cycle stability. DETAILED DESCRIPTION
[0051] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.
[0052] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.
[0053] Preparation Example 1
[0054] This preparation example provides a porous carbon material and a preparation method thereof.
[0055] (1) 20 g of water-soluble phenolic resin and 18 g of hexamethylenetetramine were dispersed in 5 g of ammonia water, and deionized water was continuously added and stirred thoroughly to make the pH of the final uniform system 8.0. Then 0.5 g of tetraethyl orthosilicate was added and stirred for 2 h. After the precipitate was separated, it was aged at 110° C. for 12 h to obtain a precursor.
[0056] (2) The precursor and zinc chloride were uniformly mixed in a mass ratio of 1:2, and the temperature was raised to 350°C in an Ar atmosphere for 2 h, and then raised to 1400°C for 2 h to obtain product 1. Product 1 was mixed with KOH in a mass ratio of 1:4, and the temperature was raised to 850°C in an Ar atmosphere for 1 h. The activated product was dealkalized by washing with water to obtain the final porous carbon material.
[0057] Preparation Example 2
[0058] This preparation example provides a porous carbon material and a preparation method thereof.
[0059] (1) 20 g of water-soluble phenolic resin and 18 g of bisphenol-A were dispersed in a urea aqueous solution, and deionized water was continuously added and stirred thoroughly to dissolve until the pH of the final uniform system was 7.5. Then 0.5 g of trimethylsiloxysilicate was added and stirred for 2 h. After the precipitate was separated, it was aged at 145° C. for 12 h to obtain a precursor.
[0060] (2) After the precursor and zinc chloride are uniformly mixed in a mass ratio of 1:2, the temperature is raised to 350°C in an Ar atmosphere and kept for 2 h, and then raised to 1400°C and kept for 2 h to obtain the final porous carbon material.
[0061] Preparation Example 3
[0062] This preparation example provides a porous carbon material and a preparation method thereof.
[0063] (1) 20 g of water-soluble phenolic resin and 12 g of hexamethylenetetramine were dispersed in a urea aqueous solution, and deionized water was continuously added and stirred thoroughly to dissolve until the pH of the final uniform system was 8.0. Then 0.5 g of tetraethyl orthosilicate was added and stirred for 2 h. After the precipitate was separated, it was aged at 110° C. for 12 h to obtain a precursor.
[0064] (2) The precursor and zinc chloride were uniformly mixed in a mass ratio of 1:2, and the temperature was raised to 350°C in an Ar atmosphere for 2 hours, and then raised to 1400°C for 2 hours to obtain product 2. Product 2 was mixed with KOH in a mass ratio of 1:2, and the temperature was raised to 850°C in an Ar atmosphere for 1 hour. After the activated product was dealkalized, the final product, a porous carbon material, was obtained.
[0065] Preparation Example 4
[0066] This preparation example provides a porous carbon material and a preparation method thereof.
[0067] (1) 20 g of water-soluble melamine resin, 18 g of hexamethylenetetramine, 5 g of ammonia water, and 10 g of deionized water were added, and the final uniform system pH was 8.8. The mixture was fully ground and infiltrated, and then aged at 110° C. for 12 h to obtain a precursor.
[0068] (2) The precursor and zinc chloride were uniformly mixed in a mass ratio of 1:2, and the temperature was raised to 350°C in an Ar atmosphere for 2 hours, and then raised to 1400°C for 2 hours to obtain product 1. Product 1 was mixed with KOH in a mass ratio of 1:4, and the temperature was raised to 850°C in an Ar atmosphere for 1 hour. After the activated product was dealkalized, the final product, a porous carbon material, was obtained.
[0069] Preparation Example 5
[0070] This preparation example provides a porous carbon material and a preparation method thereof.
[0071] (1) 20 g of water-soluble phenolic resin and 15 g of bisphenol-S were dispersed in ammonia water, and deionized water was continuously added and stirred thoroughly to make the pH of the final uniform system 8.0. Then 0.5 g of tetraethyl orthosilicate was added and stirred for 2 h. After the precipitate was separated, it was aged at 110° C. for 12 h to obtain a precursor.
[0072] (2) The precursor was heated to 800°C in an Ar atmosphere for 1 h, and then heated to 1400°C for 2 h to obtain product 3. Product 3 was mixed with KOH in a mass ratio of 1:2, and heated to 850°C in an Ar atmosphere for 1 h. After removing the alkali from the activated product, the final product, a porous carbon material, was obtained.
[0073] Preparation Example 6
[0074] This preparation example provides a porous carbon material and a preparation method thereof.
[0075] (1) 20 g of water-soluble phenolic resin and 15 g of bisphenol-S were dispersed in ammonia water, and deionized water was continuously added and stirred thoroughly to dissolve until the pH of the final uniform system was 8.0. The mixture was stirred for 2 h, and the precipitate was separated and aged at 110° C. for 12 h to obtain a precursor.
[0076] (2) The precursor was heated to 800°C in an Ar atmosphere for 1 h, and then heated to 1400°C for 2 h to obtain product 3. Product 3 was mixed with KOH in a mass ratio of 1:2, and heated to 850°C in an Ar atmosphere for 1 h. After removing the alkali from the activated product, the final product, a porous carbon material, was obtained.
[0077] Preparation Example 7
[0078] This preparation example provides a porous carbon material and a preparation method thereof.
[0079] (1) 20 g of water-soluble phenolic resin and 18 g of hexamethylenetetramine were dispersed in ammonia water, and deionized water was continuously added and stirred thoroughly to dissolve until the pH of the final uniform system was 8.0. The mixture was stirred for 2 h, and the precipitate was separated and aged at 110° C. for 12 h to obtain a precursor.
[0080] (2) After the precursor and zinc chloride are uniformly mixed in a mass ratio of 1:2, the temperature is raised to 350°C and kept for 2 h in an Ar atmosphere, then raised to 800°C and kept for 1 h, and then raised to 1400°C and kept for 2 h to obtain the final porous carbon material.
[0081] Comparative Preparation Example 1
[0082] This comparative preparation example provides a porous carbon material and a preparation method thereof.
[0083] The difference from Preparation Example 1 is that in this Preparation Example, step (2) is replaced by: after uniformly mixing the precursor and zinc chloride in a mass ratio of 1:2, heating to 1400°C under Ar atmosphere and keeping warm for 4 hours to obtain a porous carbon material.
[0084] Examples 1-7
[0085] This embodiment provides a method for preparing a silicon-carbon composite material using the porous carbon material provided in Preparation Examples 1-7.
[0086] 5 g of the prepared porous carbon material was placed in a stainless steel high-sealing muffle furnace, evacuated to <10 Pa, and maintained for 10 min. High-purity argon (99.999%) was used as a carrier gas with a flow rate of 60 mL / min, and high-purity monosilane (99.9999%) was used as a silicon source with a flow rate of 50 mL / min, and they were introduced into the furnace chamber together to perform a deposition reaction at 475 °C.
[0087] The heat preservation reaction time of Examples 1-7 is 80min, 80min, 60min, 100min, 80min, 60min and 60min respectively. After the reaction is finished, the high-purity monosilane is stopped, and the high-purity argon flow is maintained until the temperature in the furnace drops to room temperature, and the sample is taken out.
[0088] Comparative Example 1
[0089] This comparative example provides a method for preparing a silicon-carbon composite material.
[0090] The difference from Example 1 is that in this comparative example, the porous carbon material used in the example is replaced by the porous carbon material provided in Preparation Comparative Example 1.
[0091] Performance Test 1
[0092] The silicon-carbon composite materials provided in the examples and comparative examples were prepared into lithium-ion half-cells, and performance tests were performed as follows:
[0093] (1) The material mass ratio of silicon carbon electrode is active material / conductive agent (acetylene black) / binder (CMC) = 8 / 1 / 1, and 0.1% by mass of single-walled carbon nanotubes is added. The mixture is ground and mixed for 30 minutes. After a uniform mixed slurry is formed, it is uniformly coated on a copper foil using a 200 μm preparation device. The solvent is then dried in a vacuum oven at 120° C. for 12 hours. The mixture is then repeatedly rolled and compacted using a roller press and cut into 12 mm electrode discs using a slicer for standby use.
[0094] (2) Lithium-ion half-cell assembly: The electrode sheets were weighed one by one and transferred to an inert gas-protected glove box to assemble the battery. The button cell used was CR2032, the battery electrolyte was 1M LiPF6 dissolved in DEC, EC and FEC (v / v / v=1:1:0.05), and the separator was polypropylene Celgard 2500.
[0095] Electrochemical performance test: The assembled battery was subjected to constant current charge and discharge experiment in a BlueHe / Newway tester, and the mass specific capacity and cycle stability of the material were tested under 0.1C conditions.
[0096] The test results are shown in Table 1, and the unit of charge and discharge capacity is mAh / g:
[0097] Table 1
[0098]
[0099] Note: The double bond oxygen content (%) is the ratio of double bond oxygen content to total oxygen content, %.
[0100] It can be seen from the embodiments and performance tests that the porous carbon material provided by the present invention can effectively control the production of silicon oxide and silicon oxide, so that the finally formed silicon-carbon composite negative electrode material has excellent first coulombic efficiency and capacity, and high cycle stability. The capacity retention rate after 20 cycles can still reach more than 50%, and the capacity retention rate after 100 cycles can still reach more than 45% at best.
[0101] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0102] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a porous carbon material, characterized in that: The preparation method comprises the following steps: (1) dispersing an organic precursor in a solvent, then mixing with an alkali source and a cross-linking agent, and drying to obtain a pretreated product; (2) Activating and carbonizing the pretreated product to obtain the porous carbon material.
2. The preparation method according to claim 1, characterized in that: The step (1) further comprises: after dispersing the organic precursor in a solvent, adding an additive, preferably the mass of the additive is 1%-10% of the mass of the organic precursor, and preferably the solvent is water; Preferably, the additive is selected from silicate compounds.
3. The preparation method according to claim 1 or 2, characterized in that: The organic precursor is selected from soluble phenolic polymers; And / or, the alkaline source is selected from any one or a combination of at least two of ammonia water, urea or sodium carbonate; And / or, the cross-linking agent is selected from hexamethylenetetramine and / or bisphenol cross-linking agents.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step (1), the amount of the alkaline source added is such that the pH value of the mixed solution after mixing is 7.5-9; And / or, the mass ratio of the organic precursor to the cross-linking agent is 1:0.1-1.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The step (2) comprises: The pretreated product is mixed with zinc chloride, activated at 300-450° C. for 1-1.5 h, and programmed to be heated to 1200-1400° C. for carbonization for 0.5-2 h to obtain the porous carbon material; or: The pretreatment product is mixed with zinc chloride, carbonized at 1200-1400° C. for 0.5-2 h, and then mixed with hydroxide, activated at 700-900° C. for 0.5-2 h to obtain the porous carbon material; or: The pretreated product is mixed with zinc chloride, first activated at 300-450° C. for 1-1.5 h, programmed to 1200-1400° C. for carbonization for 0.5-2 h, and then mixed with hydroxide, and second activated at 700-900° C. for 0.5-2 h to obtain the porous carbon material; Preferably, in the step (2), the activation and carbonization are both carried out under an inert atmosphere.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the pretreatment product to zinc chloride is 1:2-6; And / or, the mass ratio of the pretreatment product to the hydroxide is 1:1-6; And / or, the hydroxide is selected from any one or a combination of at least two of potassium hydroxide, sodium hydroxide or lithium hydroxide.
7. The porous carbon material prepared by the preparation method according to any one of claims 1 to 6.
8. The porous carbon material according to claim 7, characterized in that: The specific surface area of the porous carbon material is more than 60% of the total oxygen content.
9. A silicon-carbon composite negative electrode material, characterized in that: The components of the silicon-carbon composite negative electrode material include the porous carbon material according to claim 7 or 8 and elemental silicon deposited on the surface of the porous carbon material.
10. A negative electrode sheet, characterized in that: Contains the porous carbon material according to claim 7 or 8 or the silicon-carbon composite negative electrode material according to claim 9.
11. An electrochemical device, characterized in that: It comprises the porous carbon material according to claim 7 or 8, the silicon-carbon composite negative electrode material according to claim 9, or the negative electrode sheet according to claim 10.
12. A vehicle, characterized in that: A negative electrode sheet according to claim 10 or an electrochemical device according to claim 11.
Citation Information
Patent Citations
Porous carbon silicon composite material and preparation method thereof
CN103840140A
Composite material for electrode, preparation method of composite material and prepared electrode
CN106847533A
Phenolic aldehyde-based carbon aerogel material and preparation method thereof
CN109734072A
Preparation method of silicon-carbon negative electrode material
CN116314791A
Spherical porous carbon particle powder and production method therefor
JP2008050237A
